2005
DOI: 10.1159/000088115
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Bloodstream Infections in a Speciality Hospital in Kuwait: 8-Year Experience

Abstract: Objectives: To determine the frequency of isolation and antibiotic-susceptibility patterns of clinically significant bacterial pathogens isolated from blood. Materials and Methods: The study was conducted over a period of 8 years (1995–2002) at Infectious Diseases Hospital (IDH), Kuwait. Demographic and clinical data were obtained from medical records. 18,535 blood cultures were analyzed. Disk diffusion method was used to perform antibiotic-susceptibility testing. Minimum inhibitory concentrations of 9 antimic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 41 publications
1
8
0
Order By: Relevance
“…Since then, similar cases have been reported from other countries (Wain et al, 1997;Threlfall & Ward, 2001;Hakanen et al, 2001). Although reduced susceptibility to ceftriaxone and ciprofloxacin has been reported previously for Salmonella enterica serotype Typhi and S. Paratyphi A isolated in Kuwait (Dimitrov et al, 2005), this report describes a case of ciprofloxacin treatment failure in a patient with enteric fever who had recently returned to Kuwait from India. The isolate in this report is different from that reported previously because it is susceptible to ceftriaxone whereas the isolates reported previously expressed reduced susceptibility to ceftriaxone (Dimitrov et al, 2005).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Since then, similar cases have been reported from other countries (Wain et al, 1997;Threlfall & Ward, 2001;Hakanen et al, 2001). Although reduced susceptibility to ceftriaxone and ciprofloxacin has been reported previously for Salmonella enterica serotype Typhi and S. Paratyphi A isolated in Kuwait (Dimitrov et al, 2005), this report describes a case of ciprofloxacin treatment failure in a patient with enteric fever who had recently returned to Kuwait from India. The isolate in this report is different from that reported previously because it is susceptible to ceftriaxone whereas the isolates reported previously expressed reduced susceptibility to ceftriaxone (Dimitrov et al, 2005).…”
Section: Discussionsupporting
confidence: 78%
“…Although reduced susceptibility to ceftriaxone and ciprofloxacin has been reported previously for Salmonella enterica serotype Typhi and S. Paratyphi A isolated in Kuwait (Dimitrov et al, 2005), this report describes a case of ciprofloxacin treatment failure in a patient with enteric fever who had recently returned to Kuwait from India. The isolate in this report is different from that reported previously because it is susceptible to ceftriaxone whereas the isolates reported previously expressed reduced susceptibility to ceftriaxone (Dimitrov et al, 2005). Treatment failures with fluoroquinolones in patients infected with S. Typhi with reduced susceptibility to ciprofloxacin have also been reported from Cameroon in Africa (Nkemngu et al, 2005) and Bangladesh in Asia (Asna et al, 2003).…”
Section: Discussionmentioning
confidence: 51%
“…To our knowledge, this is the first report of high rates of reduced susceptibility to rifampin among Brucella isolates from Egypt, suggesting the emergence of isolates with variable degrees of resistance to this drug (CLSI criteria for slow-growing bacteria). Only a few isolates (8-9%) with reduced susceptibility to rifampin have been described before in Turkey [16,23], Kuwait [24] and Mexico [18]. In another study conducted in Peru, only one Brucella isolate demonstrated reduced susceptibility to rifampin (1.0 μg/ml) [15].…”
Section: Discussionmentioning
confidence: 99%
“…Blood cultures were performed with Bactec 9120 (Becton Dickinson Diagnostic Instrument System, Sparks, Maryland, USA), a continuous-monitoring blood culture system14; details have been published previously 15. All isolates were identified by their API 20E profiles (bio Meraux, SA, France) and slide agglutination using specific Salmonella antisera (Ha, Hd, O9 and 02; Denka Seiken, Tokyo, Japan).…”
Section: Methodsmentioning
confidence: 99%